Peningkatan Hasil Belajar Luas Bangun Datar melalui Strategi Belajar Kooperatif Tipe Jigsaw bagi Siswa - Nurdasmi Nurdasmi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
Implementation of learning through Jigsaw type cooperative learning is by steps: dividing students into groups consisting of 4-6 people each group called the original group. Each origin group member is given a different topic. Every original group member who gets the same topic joins a group called the expert group. In expert groups, students discuss topics to be discussed according to the instructions of the Student Worksheet (LKS). After the discussion, each member of the expert group rejoined the original group to explain the topic discussed in the expert group. From the results of research that researchers have done, it appears that student learning outcomes have improved. The average value of students on a base score of 5.06, the actions are taken in the first cycle increased with an average of 6.9. Then the action is held again in cycle II, with an average student score reaching 8.3. From the results of this study, it can be concluded that through Jigsaw cooperative learning can improve student mathematics learning outcomes in class V UPT SDN 22 Tanah Bayang District. Therefore, it is suggested that teachers can carry out the learning process through Jigsaw cooperative learning with the aim of being able to improve student learning outcomes and interests.